1989
DOI: 10.1080/02626668909491361
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the parameters of an isolated event conceptual model from physical catchment characteristics

Abstract: There has been a trend in recent years towards the development and popularity of physically-based deterministic models. However, the application of such models is not without difficulties. This paper investigates the usefulness of a conceptual single-event model for simulating floods from catchments covering a wide variety of climatic and physiographic areas. The model has been calibrated on a group of catchments and the calibrated parameter values related to physical catchment indices. The resulting quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 12 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…However, in practice, data support is limited, and many of the required physical properties are unobservable at model grid scale, and cannot be adequately calibrated using typically available rainfall-runoff data. These and other limitations are well-known (Beven, 1989(Beven, , 2001Hughes, 1989;Binley et al, 1991;Beven and Binley, 1992;Wheater, 2002), and currently preclude realistic application to ungauged catchments. As noted above, metric models have been restricted by the constraints of relatively simple model structures, and recent developments, such as neural network models, are not obviously amenable to regionalisation.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, in practice, data support is limited, and many of the required physical properties are unobservable at model grid scale, and cannot be adequately calibrated using typically available rainfall-runoff data. These and other limitations are well-known (Beven, 1989(Beven, , 2001Hughes, 1989;Binley et al, 1991;Beven and Binley, 1992;Wheater, 2002), and currently preclude realistic application to ungauged catchments. As noted above, metric models have been restricted by the constraints of relatively simple model structures, and recent developments, such as neural network models, are not obviously amenable to regionalisation.…”
Section: Introductionmentioning
confidence: 97%
“…Attempts to define catchment similarity have been based on geographical closeness (Mosley, 1981;Hughes, 1989). Vandewiele and Elias (1995) based their study on catchment grouping of geographically continuous areas, even though neighbouring catchments within a region may be physically and hydrologically very different.…”
Section: Introductionmentioning
confidence: 99%
“…Then parameter sets can be compiled for ungauged catchments from measurable variables. During the past decades this approach has been tested by several scientists with varying success (Hughes, 1989;Servat and Dezetter, 1993;Braun and Renner, 1992;Ibrahim andCordery, 1995, Seibert, 1999;Merz and Blöschl, 2004;Parajka et al, 2005;Götzinger and Bárdossy, 2007). Seibert (1999) concluded that the general problem in the regionalisation of model parameters is the limited number of catchments usually available and that model parameters often are badly defined.…”
Section: Discussionmentioning
confidence: 99%
“…Many scientists have attempted to calculate some of these parameters in ungauged basins by using regression techniques (Jarboe and Haan, 1974) or by implementing conceptual models with high parameterization (Hughes, 1989). These approaches may provide credible results in site-specific cases but they are not widely applicable, since they incorporate significant amount of uncertainty.…”
Section: Methodsmentioning
confidence: 99%